The Rights to Health for All: Is Indonesia Fully Committed to Protected Refugees and Asylum Seekers? - R. Yahdi Ramadani; Aktieva Tri Tjitrawati; Mochamad Kevin Romadhona; Enny Narwati; Sri Endah Kinasih (JURNAL HUBUNGAN LUAR NEGERI, 2023)
Indonesia has a comparable obligation to safeguard the right to health for refugees and asylum seekers who enter its jurisdiction, notwithstanding its non-ratification of the 1951 Convention and the 1967 Protocol. The primary objective of this study is to examine the implementation of state policies on the safeguarding of the right to health for Refugees and Asylum Seekers in Indonesia. This study employs normative juridical research, which is a kind of research that examines doctrines or principles. Normative juridical research is sometimes referred to as theoretical research. The findings of this study indicate that not standing Indonesia's non-ratification of the 1951 Convention and the 1967 Protocol, the regulation pertaining to the safeguarding of refugees and asylum seekers has been included under Presidential Regulation (PERPRES) No. 125 of 2016. In conclusion, it can be inferred that the information presented supports the notion that the aforementioned points The challenge of providing adequate healthcare for refugees and asylum seekers in Indonesia is impeded by the lack of alignment between legal regulations and government policy.